Educational Psychology, Subjective Narratives of Consequences of Games Performance - Dandi, Dandi; Maria Veronica (Tinta Emas Institute, 2023)
Gaming addiction has become an increasing problem among children, teenagers and even adults in Indonesia. This study aims to examine the impact of gaming addiction on education in Indonesia, focusing on aspects such as academic performance, social behavior, and mental well-being. The research method used was a survey and interview of active gamers and non-gamers through 3 research subjects who are students at one of the campuses in Palangka Raya. The results showed that gaming addiction has a negative impact on students' academic performance. Respondents who played games more often tended to have lower grades compared to non-gamers. They also tend to be absent from school more frequently.